2020
DOI: 10.4067/s0718-18762020000200105
|View full text |Cite
|
Sign up to set email alerts
|

The Path between Personality, Self-Efficacy, and Shopping Regarding Games Apps

Abstract: The smartphone has made gaming more accessible and desirable for a wider market than ever before. Game apps are one of the most consumed and fastest growing products in the world today. Yet, few studies have thus far explored the implications of games apps consumption from a consumer perspective, addressing the transfer of abilities from one technological field to another. The main purpose of this paper is threefold: to ascertain the role of personality as a determinant of self-efficacy, to establish whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 77 publications
(162 reference statements)
0
22
0
Order By: Relevance
“…Aydın [45] surveyed 269 individuals in Turkey and found that openness among participants was positively associated with hedonic (pleasure-driven) and utilitarian (task-oriented) motivations, which were positively associated with social commerce adoption. San-Martin et al [49] conducted a survey with 366 Spanish game app players. The researchers proposed that openness was positively related to gaming self-efficacy (which was then related to online shopping self-efficacy and the intention to purchase online).…”
Section: The Influence Of the Big Five On Channel Choicementioning
confidence: 99%
See 1 more Smart Citation
“…Aydın [45] surveyed 269 individuals in Turkey and found that openness among participants was positively associated with hedonic (pleasure-driven) and utilitarian (task-oriented) motivations, which were positively associated with social commerce adoption. San-Martin et al [49] conducted a survey with 366 Spanish game app players. The researchers proposed that openness was positively related to gaming self-efficacy (which was then related to online shopping self-efficacy and the intention to purchase online).…”
Section: The Influence Of the Big Five On Channel Choicementioning
confidence: 99%
“…The researchers also concluded that trust and perceived usefulness partially mediated the effects of neuroticism on mobile commerce behavioral intentions. San-Martin et al [49] revealed that neuroticism negatively influenced gaming self-efficacy which, in turn, was positively related to online shopping self-efficacy, as well as the intention to purchase game-related products online. Piroth et al [30] hypothesized that neuroticism is related to the customer's attitude towards online grocery shopping, which should influence online grocery shopping adoption; however, neuroticism was not found to be related to attitudes toward online grocery shopping.…”
Section: The Influence Of the Big Five On Channel Choicementioning
confidence: 99%
“…Hsu et al [44] reported that users' self-efficacy of knowledge sharing positively affected users' expectation recognition, indicating that internet users will progressively master complex tasks. Self-efficacy is not only associated with the skills one masters but also with one's confidence in using them [45,46]. Overall, users with low levels of self-efficacy are less likely to use and engage in social media-related behaviors and activities than people with higher levels of self-efficacy.…”
Section: Self-efficacymentioning
confidence: 99%
“…If live-streaming users attempt to win the favor of anchors and other users on the live-streaming platform, they may be then buy additional supplements and items. Accordingly, self-efficacy is one of the ways to fulfill this goal [46]. Studies demonstrated that network and computer self-efficacy were important indicators in the prediction of online shopping [62].…”
Section: The Mediating Effect Of Self-efficacymentioning
confidence: 99%
“…Today's society is increasingly focused on technology and therefore people are progressively more dependent on it, particularly with regards to the Internet [1,2]. Mobile phones and different technological devices have made the world of video games and online shopping more accessible to everyone, making markets even more desirable and broad than before [3].…”
Section: Introductionmentioning
confidence: 99%